A Lytic Yersina pestis Bacteriophage Obtained From the Bone Marrow of Marmota himalayana in a Plague-Focus Area in China - Liang, Junrong; Qin, Shuai; Duan, Ran; Zhang, Haoran; Wu, Weiwei; Li, Xu; Tang, Deming; Fu, Guoming; Lu, Xinmin; Lv, Dongyue; He, Zhaokai; Mu, Hui; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
A lytic Yersinia pestis phage vB_YpP-YepMm (also named YepMm for briefly) was first isolated from the bone marrow of a Marmota himalayana who died of natural causes on the Qinghai-Tibet plateau in China. Based on its morphologic (isometric hexagonal head and short non-contractile conical tail) and genomic features, we classified it as belonging to the Podoviridae family. At the MOI of 10, YepMm reached maximum titers; and the one-step growth curve showed that the incubation period of the phage was about 10 min, the rise phase was about 80 min, and the lysis amount of the phage during the lysis period of 80 min was about 187 PFU/cell. The genome of the bacteriophage YepMm had nucleotide-sequence similarity of 99.99% to that of the Y. pestis bacteriophage Yep-phi characterized previously. Analyses of the biological characters showed that YepMm has a short latent period, strong lysis, and a broader lysis spectrum. It could infect Y. pestis, highly pathogenic bioserotype 1B/O:8 Y. enterocolitica, as well as serotype O:1b Y. pseudotuberculosis—the ancestor of Y. pestis. It could be further developed as an important biocontrol agent in pathogenic Yersinia spp. infection.